HYDRAULIC CONDUCTANCE AND RESPONSE TIME OF TENSIOMETERS USED IN CULTIVATIONS UNDER FERTIRRIGATION (Revista de Ciências Agroveterinárias, 2005)
The tensiometer has been largely used for proper irrigation scheduling due to its simplicity, low cost and satisfactory precision. Although there is an increasing tendency of using fertirrigation, experimental data relating this practice to the cup hydraulic conductance and response time of the tensiometer are not available. The present study aimed to evaluate the changes on the hydraulic conductance (CH) and on the response time (TR) of ceramic cups after the cups were submitted to the following treatments: (a) immersion for 30 days in fertilizer solution with increasing concentrations; (b) use to monitor water availability to pepper grown in sandy and clay soils under irrigation and fertirrigation. CH increased and TR decreased accordingly to the increasing fertilizer solution concentration after immersion; CH decreased after the field trial with pepper; fertilizers added to the irrigation water did not influence CH and TR; soil texture did not affect CH and TR at 60 kPa tension.
Keywords: conductance; tension; porous cups.